Transfer RNA genes in Drosophila mitochondrial DNA: related 5' flanking sequences and comparisons to mammalian mitochondrial tRNA genes. - Clary, D O (1983)
Genes for tRNAgly and tRNAserUCN have been identified within sequences of mtDNA of Drosophila yakuba. The tRNAgly gene lies between the genes for cytochrome c oxidase subunit III and URF3, and all three of these genes are contained in the same strand of the mtDNA molecule. The tRNAserUCN gene is adjacent to the URF1 gene. These genes are contained in opposite strands of the mtDNA molecule and their 3' ends overlap. The structures of the tRNAgly and tRNAserUCN genes, and of the four tRNA genes of D. yakuba mtDNA reported earlier (tRNAile, tRNAgln, tRNAf-met and tRNAval) are compared to each other, to non-organelle tRNAs, and to corresponding mammalian mitochondrial tRNA genes. Within 19 nucleotides upstream from the 5' terminal nucleotide of each of the Drosophila mitochondrial tRNAgly, tRNAserUCN, tRNAile, tRNAgln and tRNAf-met genes occurs the sequence 5'TTTATTAT, or a sequence differing from it by one nucleotide substitution. Upstream from this octanucleotide sequence, and separated from it by 3, 4 and 11 nucleotides, respectively, in the 5' flanking regions of the tRNAile, tRNAserUCN and tRNAgly genes occurs the sequence 5'GATGAG.